2006
DOI: 10.2478/cttr-2013-0823
|View full text |Cite
|
Sign up to set email alerts
|

Study of Growing Flue-cured Tobacco in Croatia under Various Conditions of Irrigation and Nitrogen Nutrition

Abstract: Three field experiments were conducted at the experimental station of the Tobacco Institute Zagreb in Pitomaca during the years 1990 and 1992, 1993-1996 and 1999-2000 to determine the effects of irrigation at different soil moisture levels [40-100%, 60-100%, 80-100% of plant available water, (PAW)], of different starting times of irrigation (vegetative phase, early flowering stage, continuously), and of irrigation combined with nitrogen nutrition (0, 20, 40, 60 kg/ha N) on the yields and quality of flue-cured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…All rights reserved. Cavlek, 2006;Parker, 2009;Henry et al, 2019); therefore, our results were not unexpected with the conventional genotypes NC95 and K326. However, it is interesting to note that the same pattern was not observed in the low alkaloid genotypes.…”
Section: Alkaloid Concentration: Nicotine Nornicotine Anabasine supporting
confidence: 67%
See 1 more Smart Citation
“…All rights reserved. Cavlek, 2006;Parker, 2009;Henry et al, 2019); therefore, our results were not unexpected with the conventional genotypes NC95 and K326. However, it is interesting to note that the same pattern was not observed in the low alkaloid genotypes.…”
Section: Alkaloid Concentration: Nicotine Nornicotine Anabasine supporting
confidence: 67%
“…It is well established that N application and tobacco alkaloid accumulation are positively correlated (Cavlek et al, 2006;Felipe & Long, 1988;Flower, 1999;Henry et al, 2019;Ismail & Long, 1980;McCants & Woltz, 1967;Parker, 2009;Peedin, 1999;Weybrew et al, 1983;Woltz et al, 1949); therefore, our results were not unexpected with the conventional genotypes NC95 and K326. However, it is interesting to note that the same pattern was not observed in the low-alkaloid genotypes.…”
Section: Alkaloid Concentration: Nicotine Nornicotine Anabasine and Anatabinesupporting
confidence: 66%
“…The majority of tobacco farmers reported that the food insecurity in the Urambo district is due to the depletion of soil nutrients by tobacco production. Tobacco is widely known to be a nutrient heavy feeder crop for nitrogen, phosphorus and potassium and, hence reduces soil fertility and resulting in low production to the subsequent food crops (Cavlek et al, 2006;Henry et al, 2019;Reed et al, 2019;Lisuma et al, 2020). Furthermore, tobacco-related deforestation (for curing tobacco) contributes to soil erosion and degradation of the arable land and low food production (Novotny et al, 2015).…”
Section: Social Aspects Of Tobacco Curingmentioning
confidence: 99%